Mapping Organizational Drivers of Non-Academic Staff Performance During University Autonomy Reform: Evidence from an Indonesian Public University - Ilhamuddin, Ilhamuddin; Hadi, Cholichul; Yoenanto, Nono Hery; Muallifah, Muallifah (Indonesian Psychological Research, 2026)
University autonomy reforms reshape governance structures and administrative systems, yet their implications for non-academic staff performance remain underexamined. Existing studies often interpret employee performance through individual constructs such as motivation, engagement, or job satisfaction, providing limited insight into how organizational systems shape everyday work. This study investigates how non-academic staff perceived factors influencing their performance during the transition of Universitas Brawijaya to a legal-entity public university (PTN-BH). Using inductive thematic analysis of open-ended survey responses from 114 administrative staff, the study identifies four interrelated domains shaping performance: structural job demands, organizational resources, development mechanisms, and institutional reinforcement. Administrative burden and procedural complexity constrain performance capacity, while leadership support, collegial environments, and infrastructure buffer these pressures. Staff-defined development priorities support organizational learning, and institutional reinforcement sustains long-term engagement. The study proposes a systemic theory of staff performance, showing that performance emerges from the alignment of governance structures, organizational resources, and institutional support systems in reforming universities.